Construction of four 3d–4f heterometallic pillar-layered frameworks containing left- and right-handed helical chains and a I− chemosensor1. Issue 21 (7th June 2015) - Ding, Yu-Jia; Li, Teng; Hong, Xu-Jia; Zhu, Li-Cai; Cai, Yue-Peng; Zhu, Si-Ming; Yu, Shu-Juan
<x xml:space="preserve">Abstract</x> Four 3D MOFs with good chemosensors for I− ion containing equivalent left-handed and right-handed helical chains were hydrothermally synthesized by the reactions of Ln2O3 with H3imdc and ZnSO4.